2018
DOI: 10.13189/ujer.2018.060205
|View full text |Cite
|
Sign up to set email alerts
|

High School Students' Career Decision-making Difficulties According to Locus of Control

Abstract: This study intends to elaborate upon difficulties in career decisions of high school students with different locus of control. 9th, 10th, 11th and 12th grade students aged 14-19, 282 (%55.4) females, 227 (%44.6) males totaling 509 participants involved in research located in the south of Turkey. Career Decision-Making Difficulties Questionnaire (CDDQ) and Rotter Internal-External Locus of Control Scale (RIEFCS) were used to collect data. One-way analysis of variance was conducted to compare the participants' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
0
16
1
1
Order By: Relevance
“…It can be concluded that the social cognitive career theory improves the career decision-making abilities of VHS Boyolali students. Career decision making is a process which includes not only career choices but also a commitment to carry out the necessary actions to realize those choices (Kirdök & Harman, 2018). Individuals with low career decision-making skills tend to experience more negative experiences when making career decisions because of difficulties in solving problems that require complex information management.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that the social cognitive career theory improves the career decision-making abilities of VHS Boyolali students. Career decision making is a process which includes not only career choices but also a commitment to carry out the necessary actions to realize those choices (Kirdök & Harman, 2018). Individuals with low career decision-making skills tend to experience more negative experiences when making career decisions because of difficulties in solving problems that require complex information management.…”
Section: Resultsmentioning
confidence: 99%
“…Making a career choice, difficulties arise because of the lack of information about labour market situation, professional requirements, study programmes. The other researchers' conducted studies also fix the lack of information stating, that one of the biggest difficulties in the process of decision-making is the lack of useful information or uncertain information (Kırdök & Harman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The first until the fourth step in developing career decision instruments were identifying the purpose of measuring and b) domain restriction of measuring, c) operationalization of aspects, and d) item writing. The researcher collected all components and information related to career decisions based on the psychological theory and instrument developed by Kirdök & Harman (2018). After that, the researcher constructed the scale's items based on the aspects and indicators and wrote them.…”
Section: Types Of Data and Instrumentsmentioning
confidence: 99%
“…In contrast to the development of career decision-making instruments developed in Turkey, career decision-making instruments are given to high school students. It aims to help students outline their difficulties in making future career decisions (Kirdök & Harman, 2018).…”
Section: Introductionmentioning
confidence: 99%